Different equations for determining height among the elderly: the Bambuí cohort study of aging Diferentes equações para determinação da estatura em idosos: estudo de coorte de idosos de Bambuí - Vanessa de Oliveira Siqueira; Bruna Vieira de Lima Costa; Aline Cristine Souza Lopes; Luana Caroline dos Santos; Maria Fernanda Lima-Costa; Waleska Teixeira Caiaffa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to compare measured height with estimates of height derived from equations using half arm-span measurements and assess how this affects the calculation of the body mass index (BMI) among elderly individuals. Direct height measurements of a subsample of elderly individuals from the baseline sample of the Bambuí Project were compared with estimates of height derived from equations proposed by Bassey and the WHO. The data was analyzed using the McNemar test, Lin concordance correlation coefficient (CCC) and Bland-Altman method (p < 0.05). Estimates of height using the WHO method showed a low CCC in relation to measured height. For BMI, the concordance was greater. However, with this method height was found to be underestimated so leading to the overestimation of BMI. The Bassey equation showed high concordance with measured height in elderly people over 80 years of age. With respect to BMI, the WHO method resulted in a much greater prevalence of overweight, whereas the estimates derived from the Bassey method did not differ from the results obtained from direct height measurement. Height estimates using the Bassey equation were similar to the results obtained from direct measurements, suggesting that this method is applicable. O objetivo foi comparar a estatura mensurada com a obtida por equações baseando-se na semienvergadura do braço, e avaliar o impacto sobre o índice de massa corporal (IMC). Comparou-se a medida direta da estatura e a obtida pelas equações propostas por Bassey e pela Organização Mundial da Saúde (OMS), em subamostra de idosos da linha de base do Estudo de Coorte de Idosos de Bambuí. A análise constou de testes de McNemar, coeficientes de correlação de concordância de Lin (CCC) e método de Bland & Altman (p < 0,05). Pela fórmula da OMS verificou-se baixo CCC para altura mensurada e concordância superior para IMC. Constatou-se subestimação da altura e consequente superestimação do IMC. Na fórmula de Bassey foi encontrada forte concordância com a altura mensurada em idosos com mais de 80 anos. Para o IMC (OMS) observou-se prevalência bastante superior de sobrepeso. Já a prevalência de sobrepeso (Bassey) não diferiu daquela obtida pela medida direta. A estimativa da altura obtida pela fórmula de Bassey foi semelhante à medida direta, sugerindo aplicabilidade. Já a fórmula da OMS parece subestimar a altura.